2015
DOI: 10.1016/j.bpj.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The Folding Unit of Phosphofructokinase-2 as Defined by the Biophysical Properties of a Monomeric Mutant

Abstract: Escherichia coli phosphofructokinase-2 (Pfk-2) is an obligate homodimer that follows a highly cooperative three-state folding mechanism N2 ↔ 2I ↔ 2U. The strong coupling between dissociation and unfolding is a consequence of the structural features of its interface: a bimolecular domain formed by intertwining of the small domain of each subunit into a flattened β-barrel. Although isolated monomers of E. coli Pfk-2 have been observed by modification of the environment (changes in temperature, addition of chaotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Also, the results point to an influence of K + on the enzyme turnover, as indicated by the two-fold increase in the values of apparent K cat , while the affinity for ATP, as assessed by the K m , was unaffected by the presence of excess K + in the reaction. Thus, the mechanism by which K + activates ADK is likely related to the enhanced efficiency of the phosphate transfer, instead of the affinity of ADK for ATP, as has been suggested for other members of the ribokinase family 28 , 30 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Also, the results point to an influence of K + on the enzyme turnover, as indicated by the two-fold increase in the values of apparent K cat , while the affinity for ATP, as assessed by the K m , was unaffected by the presence of excess K + in the reaction. Thus, the mechanism by which K + activates ADK is likely related to the enhanced efficiency of the phosphate transfer, instead of the affinity of ADK for ATP, as has been suggested for other members of the ribokinase family 28 , 30 .…”
Section: Discussionmentioning
confidence: 88%
“…Numerous results have demonstrated that many members of the ribokinase family of phosphotransferases can be activated by K + 25 , 26 , 28 . Structures of the E. coli ribokinase, Salmonella enterica aminoimidazole riboside kinase and E. coli phosphofructokinase-2 show a K + or the equivalent Cs + bound to a conserved site among the family members 28 , 30 , 31 . Characteristically, the K + binding site of the ribokinase family locates between two loops of the large domain, immediately adjacent to an anion hole and the ATP-binding site 28 .…”
Section: Discussionmentioning
confidence: 99%
“…HDXMS allows for localization of the changes occurring within a protein structure upon association/dissociation [6, 15]. In this experiment, a comparative analysis is usually performed between a sample of the native protein complex and a second sample characterized by: i) the addition of a chemical or temperature perturbation that induces dissociation [16]; ii) a mutant variant that shifts the equilibrium towards dissociation of the protein complex [17]; or iii) the absence of one of the binding partners, as in the case of heterocomplexes [10].…”
Section: Resultsmentioning
confidence: 99%
“…Although the aforementioned experiments were revealing, both temperature and chemically induced dissociation/unfolding are phenomena that act globally on a given protein, whereas mutations that destabilize the protein-protein interface only shift the equilibrium towards the isolated subunit. Therefore, a second line of evidence was generated based on the generation of a mutant of Pfk-2 (L93A) that destabilized the protein-protein interaction [17]. This mutant, which was confirmed by size exclusion chromatography, SAXS, analytical ultracentrifugation and enzyme kinetics to correspond to an inactive monomer at protein concentrations below 30 μM and to be more compact than the cold-denatured ensemble [16], also formed a dimer upon addition of the enzyme’s natural substrate, fructose-6-phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, these archaeal glucokinases are composed by two domains: a large α/β/α domain whose topology corresponds to a Rossmann‐like fold[2,3] that constitutes the core structure for all members of the ribokinase superfamily[4]; and a small domain composed of a five‐stranded β‐sheet, which is embellished with several α‐helices that are commonly present in monomeric members of this superfamily[5]. These domains are connected by four chain crossings due to an intertwined polypeptide topology, which has been shown to promote cooperativity across these domains in other members of the ribokinase superfamily[6].…”
Section: Introductionmentioning
confidence: 99%